Simulation of Coherent Electromagnetic Waves in Wavelength Division Multiplexing (WDM) Transmission - Rahadian Dwi Oktavia Putri; Elang Rimba Briantoko; Rohim Aminullah Firdaus; Dzulkiflih Dzulkiflih (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study analyzes the application of Wavelength Division Multiplexing (WDM) in fiber optic networks which aims to find the wavelength, WDM optical spectrum and modes, as well as the CPR estimated phase and modes. In this study WDM allows the simultaneous transmission of different data streams through a single optical fiber, using different wavelengths. This research was conducted using the python OptiCommPy module. This module is used to perform modeling of complex optical fiber transmission systems by considering the various parameters and disturbances involved in optical transmission. The results obtained from this study are that WDM networks can use full or limited wavelength conversion, depending on the wavelength conversion capability of each network node. Whereas multifiber networks use fiber pools between network nodes, and multifiber WDM networks can be implemented without or with full wavelength conversion. This research can be a guide for designing coherent electromagnetic waves in WDM transmissions using the OptiCommPy python module.